PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 014 SILIKUAN HULU KECAMATAN UKUI KABUPATEN PELALAWAN - Ritmiyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes in Science (IPA) for grade II SDN 014 Silikuan Hulu. Of the 27 students, only 12 students or 44.5% completed the results of their study, while the average value of student learning outcomes is 64.4. This learning outcome is still low by the KKM (Minimum Completeness Criteria) set at 70. Based on this, the researchers conducted a classroom action research by implementing the STAD (Student Teams Achievement Divisions) cooperative learning model with the aim to improve learning outcomes in Science. This study was conducted over two cycles, each cycle consisting of two meetings and one daily test. The instruments used were observation sheet activities of teachers and students and science achievement test. The data collection technique used is the technique of observation and testing techniques. The results showed that after the implementation of the STAD cooperative learning model, teacher and student activity increased. In the first cycle, the first meeting of teachers was categorized as moderate activity, with a total score of 16 or 66.7%. At the second meeting, it increased with a total score of 18 or 75% in the "good" category. At the first meeting of the second cycle, the total score increased to 21 or 87.5% in the "good" category. Furthermore, at the second meeting, it increased with a total score of 22 or 91.7% and categorizing them very well. Activities of students has increased at each cycle. In the first cycle of the first meeting and the second meeting of student activity is average, with a total score of the first meeting of 14 or 58.3%, and the second meeting a total score of 16 or 66.7%. In the second cycle the first meeting of the total score increased to 20 or 83.3% in the "good" category. Furthermore, at the second meeting increasing with a total score of 22 or 91.7% and categorizing them very well. Besides learning outcomes IPA also increased on the basis of the average scores of learning outcomes was 64.4. In the first cycle increased to 79.8. In the second cycle the average value increased to 84.3. Besides classical completeness in each cycle to increase the initial data completeness students 44.4% or 12 students. In the first cycle the number of students who pass are 21 students or 77.8%. In the second cycle students' mastery learning increased with 26 students or 96.3%. It shows in the classical class is also declared complete.